Nation, Militär und Gesellschaft Die französische Nationalgarde in Rennes, Lyon und Paris, 1814-1848 - Dröber, Axel (Pariser Historische Studien, 2022)
The National Guard, which emerged from the Revolution, left a lasting mark on French public life and institutions. For the monarchy restored in 1814, it was an indispensable upholder of order and occupied a central place in the Bourbons' external political representation. At the same time, it had become a sign of political maturity and social distinction. It conveyed bourgeois identity and social status, on which the following regime of Louis-Philippe was also built. Axel Dröber traces the history of the National Guard of Rennes, Lyon and Paris during the Restoration and the July Monarchy. He examines the organisational forms of the armed citizens and their relationship to the administration and government. The focus is on the legacy of the French Revolution, which shaped society well into the 19th century and had a lasting influence on discipline and obedience within the country's forces tasked with upholding order.